2022
DOI: 10.12662/2359-618xregea.v11i2.p110-126.2022
|View full text |Cite
|
Sign up to set email alerts
|

Subjetivação E Adoecimento No Trabalho Policial Militar À Luz Da Psicodinâmica

Abstract: O trabalho policial militar é marcado por um contínuo processo de exposição a violências reais e simbólicas. Nesse sentido, este estudo tem como objetivo identificar como os policiais militares do Distrito Federal percebem os efeitos deletérios da organização do trabalho na saúde física e mental. De natureza qualitativa, o estudo utilizou-se de pesquisa documental e entrevistas, tratadas por meio da análise de conteúdo. Os resultados auferidos demonstram que a organização do trabalho policial militar possui si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…Concurring with the results of this study, studies have shown that, in relation to sociodemographic aspects, there was greater participation by men (13) , with a prevalent age range of 30 to 39 years (42.1%) (14) , married or in a stable union, with a decreasing number of children, ranging from 0 to 4 children, with the majority (44.2%) having no children (15) , and greater adherence to the privates (16) . Regarding cognitive abilities, they are more likely to decline in all domains as time passes (17) , including memory, perception, language, executive functions and attention (18) .…”
Section: Discussionsupporting
confidence: 81%
“…Concurring with the results of this study, studies have shown that, in relation to sociodemographic aspects, there was greater participation by men (13) , with a prevalent age range of 30 to 39 years (42.1%) (14) , married or in a stable union, with a decreasing number of children, ranging from 0 to 4 children, with the majority (44.2%) having no children (15) , and greater adherence to the privates (16) . Regarding cognitive abilities, they are more likely to decline in all domains as time passes (17) , including memory, perception, language, executive functions and attention (18) .…”
Section: Discussionsupporting
confidence: 81%
“…Assim como nos resultados dessa pesquisa, estudos mostraram que, em relação aos aspectos sociodemográficos, houve maior participação no sexo masculino (13) , com faixa etária prevalente de 30 a 39 anos (42,1%) (14) , casados ou em união estável, com número de filhos cada vez menor, variando entre 0 a 4 filhos, sendo que a maioria (44,2%) não possuía filhos (15) e maior adesão à graduação de praças (16) .…”
Section: Discussionunclassified